23. Paediatric neuromuscular ultrasound study: Inter-operators agreement. Issue 1 (January 2015) - Molesti, E.; Marinoni, M.; Lolli, F.; Gallerini, A.; Trapani, S.; Lori, S.
<x xml:space="preserve">Abstract</x> Paediatric neuromuscolar diseases are clinically heterogeneous, progressive and disabling, often requiring invasive, uncomfortable and expensive investigations. Ultrasonographic evaluation of neuromuscular diseases is an highly specific and sensitive first level screening-tool but only few paediatric normative data were reported. We performed a wide muscular ultrasound (MUS) study on 120 healthy children (2–16 y old), evaluating muscular echogenicity and thickness. All values were indipendently analyzed off-line and measured by two Neurosonologists (SL and EM) upon training and test standardization. The agreement between the two measurements was evaluated by the statistic Bland–Altman test. We report the statistical results obtained with measurements performed by two operators in 20 children. For each subject we analyzed both echogenicity and thickness of 5 muscles: Tibialis Anterior, Rectus Femoris, Biceps brachialis, Flexores of Forearm and Gastrocnemius medialis. The statistical Bland Altman analysis showed no significant differences between the measurements performed by two operators with a negligible bias for both echogenicity's and thickness' measurements of all evaluated muscles. These results suggest that our muscular ultrasound (MUS) study protocol, performed after a preliminary training and test standardization, is a reliable technique useful to collect paediatric normative data.